American Indian prehistory as written in the mitochondrial DNA: a review - WALLACE DC; TORRONI, ANTONIO (1992)
Native Americans have been divided into three linguistic groups: the reasonably well-defined Eskaleut and Nadene of northern North America and the highly heterogeneous Amerind of North, Central, and South America. The heterogeneity of the Amerinds has been proposed to be the result of either multiple independent migrations or a single ancient migration with extensive in situ radiation. To investigate the origin and interrelationship of the American Indians, we examined the mitochondrial DNA (mtDNA) variation in 87 Amerinds (Pima, Maya, and Ticuna of North, Central, and South America, respectively), 80 Nadene (Dogrib and Tlingit of northwest North America and Navajo of the southwest North America), and 153 Asians from 7 diverse populations. American Indian mtDNAs were found to be directly descended from five founding Asian mtDNAs and to cluster into four lineages, each characterized by a different rare Asian mtDNA marker. Lineage A is defined by a HaeIII site gain at np 663, lineage B by a 9-bp deletion between the COII and tRNA(Lys) genes, lineage C by a HincII site loss at np 13259, and lineage D by an AluI site loss at np 5176. The North, Central, and South America Amerinds were found to harbor all four lineages, demonstrating that the Amerinds originated from a common ancestral genetic stock. The genetic variation of three of the four Amerind lineages (A, C, and D) was similar with a mean value of 0.084%, whereas the sequence variation in the fourth lineage (B) was much lower, raising the possibility of an independent arrival. By contrast, the Nadene mtDNAs were predominantly from lineage A, with 27% of them having a Nadene-specific RsaI site loss at np 16329. The accumulated Nadene variation was only 0.021%. These results demonstrate that the Amerind mtDNAs arose from one or maybe two Asian migrations that were distinct from the migration of the Nadene and that the Amerind populations are about four times older than the Nadene.